SR calcium handling dysfunction, stress-response signaling pathways, and atrial fibrillation - Ai, Xun (Frontiers in Physiology, 2015)
Atrial fibrillation (AF) is the most common sustained arrhythmia. It is associated with a markedly increased risk of premature death due to embolic stroke and also complicates co-existing cardiovascular diseases such as heart failure. The prevalence of AF increases dramatically with age, and aging has been shown to be an independent risk of AF. Due to an aging population in the world, a growing body of AF patients are suffering a diminished quality of life and causing an associated economic burden. However, effective pharmacologic treatments and prevention strategies are lacking due to a poor understanding of the molecular and electrophysiologic mechanisms of AF in the failing and/or aged heart. Recent studies suggest that altered atrial calcium handling contributes to the onset and maintenance of AF. Here we review the role of stress-induced calcium signaling dysfunction in atrial arrhythmogenesis in the aged and failing heart.